Corrosion properties of aluminized 16Mo3 steel - Karpe, Blaž; Prijatelj, Klara; Bizjak, Milan; Kosec, Tadeja (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Chromium-molybdenum steel (16Mo3) is widely used in petroleum, gas, automotive, and construction industries due to its good oxidation resistance and mechanical properties at moderately elevated temperatures. The aim of the research was to evaluate the corrosion susceptibility of 16Mo3 steel in hot rolled and aluminized states. Aluminization was performed by diffusion pack aluminization process at 900 °C/2h and 730 °C/4h, respectively. Electrochemical corrosion testing included measuring open circuit potential (EOCP), linear polarization resistance (LPR), potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS) in potassium phosphate buffer (KH2PO4, pH = 7). Optical microscopy (OM), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) have been used for surface layer microstructure characterization before and after corrosion tests. It has been demonstrated that corrosion resistance of aluminized steel is increased substantially. Corrosion properties are related to the structure and properties of intermetallic phase (FeAl, FeAl2 and Fe2Al5) formed on the surface of 16Mo3 steel.
Keywords: aluminide coatings; aluminized steel; aluminizing; electrochemical corrosion investigation; 16Mo3 steel